Compliance of balanced housing policy in the Philippines: the case of Davao City - Pampanga, Dario Gallares (2014)
The Philippines have quintessentially suffered setbacks in providing the housing needs for the underprivileged and homeless urban poor. The reformist policy through the balanced housing principle of the Urban Development and Housing Act (UDHA) has augured well as a strategy to cope with the socialized housing requirement brought by rapid urbanization. This paper assesses the compliance of balanced housing policy by the State and the private housing developers in the city of Davao. The study explores the mechanisms used by government to ensure compliance and the modalities availed by housign developers, and provide policy recommendation for the efficient implementation and compliance with the policy. Although there was compliance from the private sector, the policy was tweaked which resulting in considerable loss of socialized housing units in Davao City due to ambiguous application of balanced housing policy. Equally significant difficulty for an efficient implementation is the weak administrative mechanisms, causing a failure in the compliance and monitoring aspects, coupled with lack of understanding and the determination to implement the balanced housing policy. Thus, the government of Davao city needs to approach the growing urban homelessness with resolve and urgency thereby accelerating the production of socialized housing through the balanced housing policy.